Endothelial cell CD36 mediates stroke-induced brain injury via BBB dysfunction and monocyte infiltration in normal and obese conditions. Issue 6 (June 2023) - Kim, Il-doo; Ju, Hyunwoo; Minkler, Joseph; Jiang, Roselyn; Singh, Abhilasha; Sharma, Roopa; Febbraio, Maria; Cho, Sunghee
CD36 expressed in multiple cell types regulates inflammation, vascular function, and innate immunity. Specifically, CD36 in microvascular endothelial cells (ECs) signals to elicit inflammation and causes EC death. This study investigated roles for EC-CD36 on acute stroke pathology in normal and obese conditions. Obesity induced by a high-fat diet (HD) selectively increased CD36 expression in ECs, not in monocytes/macrophages, in the post-ischemic brain. Mice deficient CD36 in ECs (EC CD36−/− ) showed reduced injury size and vascular permeability in normal conditions. While control mice fed a HD developed obesity and aggravated stroke injury, EC CD36−/− mice were resistant to develop an obesity phenotype. Subjecting EC CD36−/− mice to stroke resulted in reduced injury size and BBB disruption. Moreover, the mice had reduced MCP-1 and CCR2 gene expression, resulting in reduced monocyte trafficking with improved survival and acute motor function. Reduced MCP-1 and CCR2 expression was still evident in EC CD36−/− mice subjected to severe stroke, suggesting that monocyte trafficking is an infarct-independent metabolic effect associated with specific EC-CD36 deletion. Our findings demonstrate the importance of EC-CD36 in developing vascular comorbidities and suggest that targeting EC-CD36 is a potential preventative strategy to normalize vascular risk factors, leading to improved acute stroke outcomes.